Mechanization of library procedures in the medium-sized medical library. IV. Physical characteristics of the acquisitions-cataloging record. - Roberts, J (1968)
Acquisitions-Cataloging records stored on magnetic tape by the Washington University School of Medicine Library were examined to determine frequency and average length of record components and their alphabetization requirements in a book catalog. Data from this study of 4,708 records will be used in adaptation of the Library's computer-based cataloging system to greater machine capabilities. The first of these two papers compares measurements found for WUSML records with those reported in studies of conventional catalog cards. The number of sorting positions used to alphabetize entries and causes of sort failure are examined in the second paper (Number V) which will be found on page 71 of this issue of the BULLETIN.